2020
DOI: 10.1155/2020/8051210
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Neutrophil-to-Lymphocyte Ratio Was a Predictor of Overall Survival in Small Renal Cell Carcinoma: An Analysis of 384 Consecutive Patients

Abstract: Objective. The aim of this study was to investigate the prognostic significance of the preoperative neutrophil-to-lymphocyte ratio (NLR) in small renal cell carcinoma (sRCC, ≤4 cm). Methods. This study was approved by the review board (NO.XYFY2019-KL032-01). Between 2007 and 2016, a total of 384 consecutive patients who underwent curative surgery for sRCC at our institution were evaluated. Patients were divided into high NLR and low NLR groups by plotting the NLR receiver operating characteristic curve. The Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…NLR in peripheral blood is being increasingly studied as a systemic inflammatory marker, particularly considering its rapid, widely available, and relatively inexpensive assessment through routine blood count analysis [ 13 ]. Besides lung cancer, NLR has also been proved to be associated with prognosis of small renal cell carcinoma and breast cancer [ 14 , 15 ]. The current study showed that NLR was higher in lung cancer patients compared to healthy subjects, confirming the role of NLR in the progression of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…NLR in peripheral blood is being increasingly studied as a systemic inflammatory marker, particularly considering its rapid, widely available, and relatively inexpensive assessment through routine blood count analysis [ 13 ]. Besides lung cancer, NLR has also been proved to be associated with prognosis of small renal cell carcinoma and breast cancer [ 14 , 15 ]. The current study showed that NLR was higher in lung cancer patients compared to healthy subjects, confirming the role of NLR in the progression of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline neutrophil to lymphocyte ratio (NLR) has been shown to have a negative prognostic association with RCC and to predict a more aggressive phenotype [ 70 , 71 , 72 ]. While the poor prognostic association of PD-L1 expression appears to be mitigated by immunotherapy [ 8 , 9 , 10 ], this does not appear to be the case for NLR.…”
Section: Neutrophil To Lymphocyte Ratiomentioning
confidence: 99%
“…However, the NLR has already demonstrated its prognostic value for mRCC prior to the advent of immune checkpoint inhibitors [12][13][14][15][16][17][18][19]. In addition, the NLR was also shown to be prognostic for improved disease-free survival and OS in the non-metastatic setting after nephrectomy [20,21]. Therefore, while NLR has shown a continued role as a prognostic biomarker, its role as a predictive biomarker is uncertain in terms of differentiating subsets of patients with mRCC who are more likely to benefit from immunotherapy.…”
Section: Introductionmentioning
confidence: 99%